ChatGPT in Plastic and Reconstructive Surgery - Sharma, Sanjeev Chaand; Ramchandani, Jai Parkash; Thakker, Arjuna; Lahiri, Anindya (Indian Journal of Plastic Surgery, 2023)
Background Chat Generative Pre-Trained Transformer (ChatGPT) is a versatile large language model-based generative artificial intelligence. It is proficient in a variety of tasks from drafting emails to coding to composing music to passing medical licensing exams. While the potential role of ChatGPT in plastic surgery is promising, evidence-based research is needed to guide its implementation in practice.Methods This review aims to summarize the literature surrounding ChatGPT's use in plastic surgery.Results A literature search revealed several applications for ChatGPT in the field of plastic surgery, including the ability to create academic literature and to aid the production of research. However, the ethical implications of using such chatbots in scientific writing requires careful consideration. ChatGPT can also generate high-quality patient discharge summaries and operation notes within seconds, freeing up busy junior doctors to complete other tasks. However, currently clinical information must still be manually inputted, and clinicians must consider data privacy implications. Its use in aiding patient communication and education and training is also widely documented in the literature. However, questions have been raised over the accuracy of answers generated given that current versions of ChatGPT cannot access the most up-to-date sources.Conclusions While one must be aware of its shortcomings, ChatGPT is a useful tool for plastic surgeons to improve productivity for a range of tasks from manuscript preparation to healthcare communication generation to drafting teaching sessions to studying and learning. As access improves and technology becomes more refined, surely more uses for ChatGPT in plastic surgery will become apparent.
Keywords: ChatGPT; artificial intelligence; large language models; Chatbot